Transformasi Dakwah di Era Digital: Studi Kasus Ustadz Hanan Attaki di Media Sosial - Siti Lutfi Latifah; Mei Nursasi; Nunung Nurhayati Nufus; Ade Maulana; Siti Rohmah; Linah; Badrudin; Siti Rodiah (STAI Bumi Silampari, 2026)
The development of digital technology has transformed the landscape of Islamic da‘wah through the emergence of social media platforms as broader and more interactive channels for conveying religious messages. This study examines the digital da‘wah strategies employed by Ustadz Hanan Attaki in reaching audiences in the digital era, highlighting the effectiveness of using conversational language, appealing visuals, and approaches that resonate with everyday life. Using a qualitative research method with a case study approach, this study analyzes how social media can serve as an effective tool for delivering Islamic teachings to younger generations. The findings show that the digital strategies implemented successfully enhance audience engagement, yet they also face challenges such as the simplification of Islamic teachings, dependence on platform algorithms, and the potential commercialization of da‘wah content. Therefore, adaptive strategies are needed—ones that prioritize not only popularity but also the depth and substance of Islamic teachings. This study contributes to the development of a more effective and contextual model of digital da‘wah and provides recommendations for preachers in optimizing the use of digital media.